1) 3m + 2n підставляємо:(3×(-2); 3×4) + (2×3; 2×(-1)) = (-6; 12) + (6; -2) = (0; 10)
2) -1/2 m + 2n
((-1\2) × (-2); (-1\2) × 4) + (2×3; 2×(-1)) = (1; -2) + (6; -2) = (7; -4)
3) m - 3n
(-2; 4) - (3×3; 3×(-1)) = (-2; 4) - (9; -3) = (-11; 7)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1) 3m + 2n підставляємо:
(3×(-2); 3×4) + (2×3; 2×(-1)) = (-6; 12) + (6; -2) = (0; 10)
2) -1/2 m + 2n
((-1\2) × (-2); (-1\2) × 4) + (2×3; 2×(-1)) = (1; -2) + (6; -2) = (7; -4)
3) m - 3n
(-2; 4) - (3×3; 3×(-1)) = (-2; 4) - (9; -3) = (-11; 7)